Gamification tailored for novelty effect in distance learning during COVID-19 - Kratochvil, Tomas; Vaculik, Martin; Macak, Martin (Frontiers in Education, 2023)
The pandemic led to an increase of online teaching tools use. One such tool, which might have helped students to stay engaged despite the distance, is gamification. However, gamification is often criticized due to a novelty effect. Yet, others state novelty is a natural part of gamification. Therefore, we investigated whether gamification novelty effect brings incremental value in comparison to other novelties in a course. We created achievement- and socialization-based gamification connected to coursework and practice test. We then measured students’ behavioral engagement and performance in a quasi-experiment. On the one hand, results show ICT students engaged and performed moderately better in a gamified condition than in control over time. On the other hand, BA course results show no difference between gamified and practice test condition and their novelty effect. We conclude an external gamification system yields better results than a classical design but does not exceed practice tests effect.